PENGARUH WAKTU TUNGGU TERHADAP KEPUASAN PASIEN PSIKIATRI RAWAT JALAN DI TEMPAT PENDAFTARAN PASIEN (TPP) RUMAH SAKIT JIWA MUTIARA SUKMA PROVINSI NUSA TENGGARA BARAT - Yulia Rohmiati Hamri; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Wahyu Aprilyaningsih (Nusadaya Journal of Multidiciplinary Studies, 2024)
This study aims to analyze the effect of waiting time on the satisfaction of psychiatric outpatients at the Patient Registration Unit (TPP) of Rumah Sakit Jiwa Mutiara Sukma, Nusa Tenggara Barat Province. A quantitative approach was employed using simple linear regression analysis to examine the relationship between waiting time and patient satisfaction levels. The regression results showed a coefficient value of 0.209 with a significance value of 0.524 (> 0.05), indicating that waiting time does not have a statistically significant effect on the satisfaction of psychiatric outpatients. The R Square value of 0.015 suggests that only 1.5% of the variation in patient satisfaction can be explained by the waiting time variable, while the remaining 98.5% is influenced by other factors outside the model, such as the attitude of medical staff, waiting room comfort, clarity of information, and patients’ emotional conditions. Although statistically insignificant, waiting time remains an important component of service delivery as it may influence patients’ psychological perceptions. For patients with mental disorders, the waiting process is associated with feelings of safety, calmness, and being valued; therefore, it must be managed with empathy and support. These findings highlight that service quality improvement should not only focus on time efficiency but also on a humanistic approach, staff engagement, and a supportive environment that promotes patients’ psychological recovery.